2011
DOI: 10.1016/j.schres.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Pre-illness cannabis use and the early course of nonaffective psychotic disorders: Associations with premorbid functioning, the prodrome, and mode of onset of psychosis

Abstract: Introduction-Limited research indicates that pre-illness cannabis use may result in an earlier age at onset of psychosis, though little is known about the influence of prior cannabis use on the premorbid and prodromal phases. This study examined effects of prior or concurrent cannabis (as well as nicotine and alcohol) use on: (1) early adolescent (12-15 years) premorbid functioning, (2) late adolescent (16-18 years) premorbid functioning, (3) two features of the prodrome, and (4) mode of onset of psychosis.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 44 publications
(55 reference statements)
4
21
0
Order By: Relevance
“…The substance most commonly used is cannabis, followed by cocaine, amphetamine, hallucinogen and other drugs (Allebeck et al, 1993;Hambrecht and Häfner, 2000;Compton et al, 2009Compton et al, , 2011. Moreover high frequency of polysubstance abuse and misuse are reported Barnett et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substance most commonly used is cannabis, followed by cocaine, amphetamine, hallucinogen and other drugs (Allebeck et al, 1993;Hambrecht and Häfner, 2000;Compton et al, 2009Compton et al, , 2011. Moreover high frequency of polysubstance abuse and misuse are reported Barnett et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(Cantwell et al, 1999;Veen et al, 2004;Henquet et al, 2005;Mauri et al, 2006;Koskinen et al, 2010;Mazzoncini et al, 2010;Barrigón et al, 2010). Several studies on schizophrenia have reported that patients with SUD have worse premorbid social functioning (Sevy et al, 2010;Mazzoncini et al, 2010;Compton et al, 2011;Schimmelmann et al, 2011), more severe symptoms at onset (Gearon and Bellack, 2000;Dawe et al, 2011), lower compliance and worse treatment response, thus more inappropriate use of mental health services, (Lambert et al, 2005;de Haan et al, 2007;Schimmelmann et al, 2011) with higher mental health costs (Bartels et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of first-episode schizophrenia studies also suggest that the profile of cognitive functioning is similar to that of patients with chronic schizophrenia, with generalized impairment across the majority of cognitive domains overlaid with more selective impairments in memory and learning, executive functioning, attention, and speed of information processing [16].…”
Section: Discussionmentioning
confidence: 98%
“…Many of the drug-induced psychoses in the present study were of this sort: most mimicked classic schizophrenia; a few resembled delusional disorder or bipolar disorder. In some instances, however, the marijuana (with or without concomitant use of other drugs) may have unleashed a true schizophrenia earlier than it would have manifested itself, had not the adolescent abused the drugs [28,29]. Since drug abuse usually begins around the time of puberty, it is not easy to determine whether a particular adolescent drug-abuser who appears schizophrenic at say, sixteen, was destined to have shown signs of the classic psychosis at twenty, but for the early drug abuse.…”
Section: Discussionmentioning
confidence: 99%